2006
DOI: 10.1634/theoncologist.11-7-790
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy of Advanced Hepatocellular Carcinoma: How Hopeful Should We Be?

Abstract: Worldwide, hepatocellular carcinoma (HCC) is the fifth most common cancer and the third most common cause of cancer-related death. In the U.S., 18,510 new cancers of the liver and intrahepatic bile duct are expected in 2006, with an estimated 16,200 deaths. The incidence rates for HCC in the U.S. continued to rise steadily through 1998 and doubled during the period 1975-1995. Unresectable or metastatic HCC carries a poor prognosis, and systemic therapy with cytotoxic agents provides marginal benefit. A majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
186
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(191 citation statements)
references
References 102 publications
1
186
0
4
Order By: Relevance
“…Objective tumor response rate to single-agent cytotoxic therapies is usually less than 10%, and no survival benefit has been observed [372][373][374][375][376]. An earlier randomized trial comparing doxorubicin, 60-75 mg/m 2 every 3 weeks, with no treatment indicated a borderline improvement in overall survival (10.6 vs. 7.5 weeks) for patients who received doxorubicin [377].…”
Section: Cytotoxic Therapy: Single Agent and Combinationmentioning
confidence: 99%
“…Objective tumor response rate to single-agent cytotoxic therapies is usually less than 10%, and no survival benefit has been observed [372][373][374][375][376]. An earlier randomized trial comparing doxorubicin, 60-75 mg/m 2 every 3 weeks, with no treatment indicated a borderline improvement in overall survival (10.6 vs. 7.5 weeks) for patients who received doxorubicin [377].…”
Section: Cytotoxic Therapy: Single Agent and Combinationmentioning
confidence: 99%
“…Up to 70% of patients with hepatocellular carcinoma have been suffering from limited treatment options because of late diagnosis and/or advanced stage of the disease when, however, surgical treatments including liver transplantation and hepatectomy as well as regional therapy are not feasible. Currently, there is no proven effective conventional systemic chemotherapy for patients with advanced hepatocellular carcinoma because of the inherent chemoresistant nature of hepatocellular carcinoma and with intolerable cytotoxicity, resulting in the dismal prognosis of these patients (2)(3)(4). Hepatocellular carcinoma is a heterogeneous disease in terms of etiology, molecular, and carcinogenic mechanisms as well as biologic behaviors, which can collectively contribute to diverse mechanisms of chemoresistance among patients with hepatocellular carcinoma (5).…”
Section: Introductionmentioning
confidence: 99%
“…1 Systemic therapy with cytotoxic agents provides only marginal benefit. 2,3 The molecular biology of carcinogenesis and tumor progression of HCC has been increasingly understood after intensive research in recent years. 4,5 Among these advances, several important intracellular signaling pathways such as the Ras/Raf/Mek/ ErK and PI3K/Akt/mTOR pathways have been implicated.…”
Section: Introductionmentioning
confidence: 99%